Implementasi Pendidikan Karakter Pada Siswa Di Pertubuhan Muhibbin Melaka Malaysia - Danny Abrianto; Khairil Anwar Nasution; T Aldi Rizky Pratama (Universitas Pahlawan Tuanku Tambusai, 2025)
Character education is a crucial element in shaping students' personality and morality, especially amid the challenges of globalization that threaten cultural values and national identity. This study aims to describe the implementation of character education at Madrasah Pertubuhan Kebajikan Al-Muhibbin Melaka, Malaysia. The research employed a descriptive qualitative method, with data collected through observation, in-depth interviews, and documentation. The research subjects included the head of the madrasah, teachers, and selected students using purposive sampling. The findings reveal that character education is implemented in an integrated manner through both intracurricular and extracurricular activities. Core values such as discipline, responsibility, social awareness, tolerance, and moral integrity are consistently instilled in students’ daily behavior. Activities such as congregational prayer, Qur’an recitation, religious studies, community service, and daily moral assessments serve as effective means of character formation. The study concludes that the madrasah successfully fosters a conducive educational environment for the holistic development of student character.